P247 CURBO2–65 is superior to CURB-65 in predicting readmissions, length of stay and identifying sicker patients. (14th November 2013) - Molugu, C; Falconer, W; Singer, A; Disney, A; Stockton, P; McCulloch, L; Lewis, A; Peers, V
Abstract : Introduction and Objectives: Community Acquired Pneumonia (CAP) accounts for a significant proportion of hospital admissions and is a common cause of mortality and morbidity in UK. CURB-65 is recommended by BTS and widely used to stratify patients according to severity and guide initial treatment (1) . As oxygen is not part of the CURB-65 assessment, we incorporated Oxygen saturations (SATS) to CURB-65 to create CURBO2–65 score. We then compared CURBO2–65 with CURB65 to assess if CURBO2–65 would be a superior indicator in identifying patients with severe pneumonia. Methods: We retrospectively reviewed electronic medical records of patients who were diagnosed with CAP between December 2012 and January 2013. CURB-65 was documented for all the cases whilst CURBO2–65 scores were retrospectively calculated. A score of 1 was allocated if SATS were <88% for COPD patients or <94% for non-COPD patients. A score of 1 was added if they were on supplemental Oxygen to maintain their SATS. Results: (see Table 1 ) Total of 269 admissions with CAP were analysed. 12 of these 269 patients were admitted to critical care. 2/12 (ITU) patients had a CURBO2–65 score of ≤ 2 whilst 7/12 had a CURB-65 score ≤2. CURBO2–65 also had a better correlation with MEWS than CURB-65 on admission (p < 0.05). Only 10% of cases with a CURBO2–65 score of 0–1 (5/50) were readmitted within 28 days compared to 15% of cases with a CURB-65 score 0–1 (13/87). There was a statistically significant correlation between length of stay and CURB-65 (p = 0.0085) and CURBO2–65 (p = 0.0014). Conclusions: CURBO2–65 is superior to CURB-65 in identifying sicker cohort of patients, predicting readmission rates and length of stay. Adding Oxygen to CURB-65 is simple and can be undertaken even in primary care setting (CRBO2–65 instead of CRB-65). References: Lim WS et al . Defining community acquired pneumonia severity on presentation to hospital: an international derivation and validation study. Thorax 2003;58:377–382.